Data from: Towards an integrated database on Canadian ocean resources: benefits, current states, and research gaps - Cisneros-Montemayor, Andrés M.; Cheung, William Wai Lung; Bodtker, Karin; Teh, Louise; Steiner, Nadja; Bailey, Morgan; Hoover, Carie; Sumaila, Ussif Rashid (Borealis, 2021)
AbstractOceanic ecosystem services support a range of human benefits, and Canada has extensive research networks producing growing data sets. We present a first effort to compile, link, and harmonize available information to provide new perspectives on the status of Canadian ocean ecosystems and corresponding research. The metadata database currently includes 1094 individual assessments and data sets from government (n = 716), nongovernment (n = 320), and academic sources (n = 58), comprising research on marine species, natural drivers and resources, human activities, ecosystem services, and governance, with data sets spanning 1979–2012 on average. Overall, research shows a strong prevalence towards single-species fishery studies, with an underrepresentation of economic and social aspects, and of the Arctic region in general. Nevertheless, the number of studies that are multispecies or ecosystem-based have increased since the 1960s. We present and discuss two illustrative case studies — marine protected area establishment in Canada and herring resource use by the Heiltsuk First Nation — highlighting the potential use of multidisciplinary data sets drawn from metadata records. Identifying knowledge gaps is key to achieving the comprehensive, accessible and interdisciplinary data sets and subsequent analyses necessary for new sustainability policies that meet both ecological and socioeconomic needs.